2018
DOI: 10.1371/journal.pntd.0006412
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Rift Valley fever in humans and animals from Kabale district in Southwestern Uganda, 2016

Abstract: BackgroundRift Valley fever (RVF) is a zoonotic disease caused by Rift Valley fever virus (RVFV) found in Africa and the Middle East. Outbreaks can cause extensive morbidity and mortality in humans and livestock. Following the diagnosis of two acute human RVF cases in Kabale district, Uganda, we conducted a serosurvey to estimate RVFV seroprevalence in humans and livestock and to identify associated risk factors.MethodsHumans and animals at abattoirs and villages in Kabale district were sampled. Persons were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 33 publications
7
54
1
Order By: Relevance
“…This region constitutes long borders with Zambia, Tanzania, Burundi, Rwanda, Uganda and South Sudan. Most of these countries are known to be endemic of Rift Valley fever [56][57][58][59][60]. It is likely that the active and uncontrolled migration of human and animal population might have played a key role in spreading of RVFV in the DRC.…”
Section: Discussionmentioning
confidence: 99%
“…This region constitutes long borders with Zambia, Tanzania, Burundi, Rwanda, Uganda and South Sudan. Most of these countries are known to be endemic of Rift Valley fever [56][57][58][59][60]. It is likely that the active and uncontrolled migration of human and animal population might have played a key role in spreading of RVFV in the DRC.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks may then be amplified by epidemic vectors, of which Culex theileri is considered the most important on the interior plateau 12 . Risk factor studies conducted during and after outbreaks in both humans and animals have identified several other environmental, human, and animal factors that may be associated with RVF outbreaks and RVFV seropositivity [13][14][15][16][17] . The presence of large water bodies was found to be associated with seropositivity in Somalia 15 and southwest Saudi Arabia 16 .…”
mentioning
confidence: 99%
“…The RVF virus is transmitted through bites of various species of Aedes and Culex mosquitoes which serve as reservoirs and amplifying vectors, respectively. The virus can also be transmitted through contact with infective animal tissues such as blood, aborted foetus and other body fluids (Nyakarahuka et al 2018). Humans have also been infected through drinking of raw, unpasteurized milk from infected animals (Ng'ang'a et al 2016).…”
Section: Rift Valley Fevermentioning
confidence: 99%